1970
DOI: 10.1161/01.res.27.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of the Atrial Systole-Ventricular Systole Interval and of Patterns of Ventricular Activation to Ventricular Function during Electrical Pacing of the Dog Heart

Abstract: In areflexic canine right heart bypass preparations, little difference in ventricular function was observed as a result of atrial pacing, sequential atrioventricular pacing, or atrial-His bundle pacing at an appropriate atrial systole-ventricular systole (As-Vs) interval. Ventricular function was depressed during ventricular pacing and during atrioventricular pacing with an inappropriate As-Vs interval. In areflexic isovolumic left ventricle preparations, ventricular function was depressed during ventricular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

1974
1974
2011
2011

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(25 citation statements)
references
References 19 publications
1
23
1
Order By: Relevance
“…In patients, changing the AV interval from 100 to 130 to 0 ms decreased cardiac output by Ϸ20%. 12,28,29 In a separate series of experiments in 5 AV-blocked dogs, however, we found that switching the AV interval from 100 to 25 to 30 ms changed cardiac output only by Ϫ10 to 3% (M. Peschar, MSc, and F.W. Prinzen, PhD, unpublished data, 1997).…”
Section: Pump Functionmentioning
confidence: 96%
“…In patients, changing the AV interval from 100 to 130 to 0 ms decreased cardiac output by Ϸ20%. 12,28,29 In a separate series of experiments in 5 AV-blocked dogs, however, we found that switching the AV interval from 100 to 25 to 30 ms changed cardiac output only by Ϫ10 to 3% (M. Peschar, MSc, and F.W. Prinzen, PhD, unpublished data, 1997).…”
Section: Pump Functionmentioning
confidence: 96%
“…The right heart bypass preparation has been described in detail elsewhere (6). Briefly, mongrel dogs weighing 20-30 kg were anesthetized with thiamylal, 20 mg/kg, and alpha chloralose, 30 mg/kg, and ventilated with a volume ventilator.…”
Section: Methodsmentioning
confidence: 99%
“…The heart was exposed through a median sternotomy and heparin (3 mg/kg) administered i.v. This preparation has been described in detail previously (7). Briefly, venous return from the cannulated superior and inferior venae cavae was directed to a reservoir from which the blood was warmed, oxygenated, and returned to the arch of the aorta for retrograde coronary artery perfusion via a calibrated occlusive roller pump.…”
Section: Isozolumic Left Ventricle Fasting Adult Mongrel Dogsmentioning
confidence: 99%